Giant Renal Angiomyolipoma without Fat Density on CT Scan: Case Report and Review of the Literature. (2010) - Nepple, Kenneth G.; Bockholt, Nathan A.; Dahmoush, Laila; Williams, Richard D.
Abstract : Giant renal angiomyolipomas have been reported, but typically have the pathognomonic finding of fat density on CT scan. We present the case of a 53-year-old male with a symptomatic, 35-cm, predominantly cystic renal mass without fat density on CT that on nephrectomy was found to be a fat-poor angiomyolipoma with predominantly epithelioid morphology weighing 17.9 kg. Giant renal angiomyolipoma without macroscopic fat density on CT scan is an exceedingly rare occurrence.